2020
DOI: 10.1002/jclp.23010
|View full text |Cite
|
Sign up to set email alerts
|

Social functioning in schizotypy: How affect influences social behavior in daily life

Abstract: Objective Social deficits are already exhibited by people at risk for schizophrenia‐spectrum disorders. Technological advances have made passive detection of social deficits possible at granular levels. Method In this real‐world study, we tested if schizotypy status (high/low) predicted two types of social behavior: (1) being around other people; and (2) actively socializing with others. We also examined if schizotypy influences relationships between social behavior and affect using subjective and objective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…This is a common approach in EAR studies (Abel & Minor, 2021; Robbins et al, 2011, 2014) and allows participants to listen to and delete files that they do not want to share with our team. Consistent with other studies, approximately 1% of files were deleted in this trial (Minor et al, 2018, 2020; Robbins et al, 2014). Second, not providing recording times to participants likely minimizes social desirability biases and limits the impact of the EAR on participants’ behavior.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is a common approach in EAR studies (Abel & Minor, 2021; Robbins et al, 2011, 2014) and allows participants to listen to and delete files that they do not want to share with our team. Consistent with other studies, approximately 1% of files were deleted in this trial (Minor et al, 2018, 2020; Robbins et al, 2014). Second, not providing recording times to participants likely minimizes social desirability biases and limits the impact of the EAR on participants’ behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Pre–post intervention data showed strong evidence of feasibility: participants in both conditions wore the EAR over 70% of their waking hours (84% in Tailored MERIT), with little change between pre–post time points. These findings aligned with past EAR assessment studies (Manson & Robbins, 2017; Minor et al, 2020) and show that asking people to wear the EAR for extended periods is a viable strategy. Our group has also shown that having participants wear the EAR for 2 days yields enough data to select social interactions, as a recent study found that our strategy resulted in a mean of >6 recorded interactions per week in those with schizophrenia (Abel et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The primary function of a normative positivity offset is to motivate for exploratory behavior. Therefore, an interesting avenue for future research is to investigate whether the diminished positivity offset adds to explaining diminished goal-directed activity that has been found in ecological momentary assessment (EMA) studies both in people with schizophrenia 2 4 , 27 and in people with elevated levels of psychosis proneness 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, another suggestion would be that the two SPQ subscales could reflect criterion variables, that is social problems might be a consequence of schizotypy rather than a defining characteristic (e.g., Minor et al, 2020;Springfield & Pinkham, 2020). That is, is someone schizotypic because he or she does not have close friends;…”
Section: Discussionmentioning
confidence: 99%